INTEGRASI PENDIDIKAN KARAKTER ANAK USIA DINI MELALUI MODEL PEMBELAJARAN BERBASIS BEYOND CENTERS AND CIRCLE TIME (BCCT) - Ismail, Ismail (Kopertais Wilayah X Jawa Tengah, 2013)
AbstractThis article presents the implementation of character education in early children setting through BCCT-based learning model. It also discusses character values that can be built and developed by this model. Since this study belongs to a literary research, the data used are from any written texts i.e. journals, books, online resources, and so on.The results show that the intended implementation consists of three main processes, planning, implementation, and evaluation. For the first step, the teacher plans learning by creating daily activity plan (RKH), weekly activity plan (RKM), one-semester plan, and annual plan. In the implementation process, the character values can be inserted in various centers including four principal steps i.e. circles step, pre-game step, at-game step, and post-game step. The teacher then evaluates his/her implementation either at the moment of learning or afterward.Having observed fifteen character values for early children produced by directorate general of early childhood education of national education minister, the value â€œdivine loveâ€ should always be appeared in each center. It hopefully can be the basis for children before loving their fellow, so that the other characters spontaneously emerge, either related to themselves or others. On the other hand, from seven centers used, the center â€œrole-playâ€ intensely plays role to help the formation of the fifteen character values.Keywords: character education, early childhood education, BCCT